Utility of magnetic resonance imaging versus histology for quantifying changes in liver fat in nonalcoholic fatty liver disease trials. Issue 6 (17th October 2013) - Noureddin, Mazen; Lam, Jessica; Peterson, Michael R.; Middleton, Michael; Hamilton, Gavin; Le, Thuy‐Anh; Bettencourt, Ricki; Changchien, Chris; Brenner, David A.; Sirlin, Claude; Loomba, Rohit
<x xml:space="preserve">Abstract</x> The magnetic resonance imaging–estimated proton density fat fraction (MRI‐PDFF) is a novel imaging‐based biomarker that allows fat mapping of the entire liver, whereas the magnetic resonance spectroscopy–measured proton density fat fraction (MRS‐PDFF) provides a biochemical measure of liver fat in small regions of interest. Cross‐sectional studies have shown that MRI‐PDFF correlates with MRS‐PDFF. The aim of this study was to show the utility of MRI‐PDFF in assessing quantitative changes in liver fat through a three‐way comparison of MRI‐PDFF and MRS‐PDFF with the liver histology–determined steatosis grade at two time points in patients with nonalcoholic fatty liver disease (NAFLD). Fifty patients with biopsy‐proven NAFLD who participated in a randomized trial underwent a paired evaluation with liver biopsy, MRI‐PDFF, and MRS‐PDFF at the baseline and 24 weeks. The mean age and body mass index were 47.8 ± 11.7 years and 30.7 ± 6.5 kg/m2, respectively. MRI‐PDFF showed a robust correlation with MRS‐PDFF both at week 0 and at week 24 (r = 0.98, P < 0.0001 for both). Cross‐sectionally, MRI‐PDFF and MRS‐PDFF increased with increases in the histology‐determined steatosis grade both at week 0 and at week 24 (P < 0.05 for all). Longitudinally, patients who had a decrease (≥1%) or increase (≥1%) in MRI‐PDFF (confirmed by MRS‐PDFF) showed a parallel decrease or increase in their body weight and serum alanine aminotransferase and aspartate aminotransferase levels at week 24 (P < 0.05). This small increase or decrease in liver fat could not be quantified with histology. Conclusion: In this longitudinal study, MRI‐PDFF correlated well with MRS‐PDFF and was more sensitive than the histology‐determined steatosis grade in quantifying increases or decreases in the liver fat content. Therefore, it could be used to quantify changes in liver fat in future clinical trials. (Hepatology 2013; 58:1930–1940)